KURIKULUM DAN PERENCANAAN - Etika Pujianti; Ike Krismawati; Ilham Jaya Abd Rauf; Hanief Abdillah Arif; Heru Sandi Susilo; Irwan B (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transformation of education in the twenty-first century has shifted the curriculum paradigm from merely an administrative document into a strategic instrument for improving educational quality. This transformation has become increasingly complex due to the emergence of the Fourth Industrial Revolution, Society 5.0, Artificial Intelligence, digital learning, and the implementation of the Independent Curriculum, which require Islamic educational institutions to develop adaptive, flexible, and outcome-oriented curricula. From the perspective of Islamic Educational Management, curriculum development should not only focus on academic achievement but also on fostering spirituality, morality, and Islamic values comprehensively. This study aims to analyze the concept of curriculum and educational planning in Islamic education from the perspective of Islamic Educational Management, identify challenges in curriculum implementation during the digital transformation era, and formulate a curriculum development model oriented toward Continuous Quality Improvement. The study employs a qualitative approach using library research. Data were collected from academic books, reputable national and international journal articles, government policy documents, and previous research. The analysis was conducted through content analysis and literature synthesis. The findings reveal that successful curriculum implementation depends on systematic planning, stakeholder participation, technological adaptability, and the integration of Islamic values. The integration of Outcome-Based Education, the Independent Curriculum, digital learning technologies, and Continuous Quality Improvement contributes significantly to improving educational quality and institutional competitiveness. Furthermore, visionary leadership, professional governance, and competent human resources are essential factors in developing an innovative, sustainable, and globally competitive Islamic education curriculum.